Merajut Pemikiran Kritis dengan Penerapan Nilai Nilai Qur'ani Sosial pada Anak Usia Sekolah - Gita Dwi Mutia; Fadilla, Eva Siti; Wulandari, Putri (STIKes Ibnu Sina Ajibarang, 2025)
. This study aims to develop critical thinking in school-age children through the application of Quranic social values. This research uses a qualitative approach with a case study in elementary schools. The results show that the application of Quranic social values can improve children's critical thinking skills, such as analyzing, evaluating, and problem-solving. This study also shows that the application of Quranic social values can help children develop good character, such as empathy, tolerance, and cooperation. This study has important implications for education for school-age children, especially in developing critical thinking and good character.